O Modelo Espiral no Planejamento de um Curso: uma Experiência - Barreira, Vânia Bernadete; Craesmeyer, Gisele M. S. (The ESPecialist, 2012)
This paper points out some advantages of the spiral syllabus over the step-by-step model. It reports on an experience of course design based on the spiral model and presents an example of a teaching point approached according to that model.